2016
DOI: 10.1007/s40615-016-0230-3
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic and Gender Differences in Help Seeking for Substance Disorders Among Black Americans

Abstract: This paper uses the National Survey of American Life (NSAL) to examine within group differences regarding help-seeking for substance disorders among a U.S. sample of African American and Caribbean Black men and women. We examined ethnic and gender differences in the type of providers sought for substance disorder treatment, as well as reasons for avoiding treatment. Results indicate that overall, few ethnic differences exist; however, African Americans are more likely than Caribbean Blacks to seek help from hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Another key distinction between African-American and African-Caribbean women relates to help-seeking behaviors. According to Redmond et al ( 2017 , p. 312), both African-American and African-Caribbean groups report avoiding treatment for substance abuse due to wanting to solve their own problems, and not identifying a need for outside help. However, African-Americans were more likely to seek help from professionals than African-Caribbean women (Redmond et al, 2017 , p. 312).…”
Section: Intersecting Cultural Identities In Health Psychologymentioning
confidence: 99%
See 1 more Smart Citation
“…Another key distinction between African-American and African-Caribbean women relates to help-seeking behaviors. According to Redmond et al ( 2017 , p. 312), both African-American and African-Caribbean groups report avoiding treatment for substance abuse due to wanting to solve their own problems, and not identifying a need for outside help. However, African-Americans were more likely to seek help from professionals than African-Caribbean women (Redmond et al, 2017 , p. 312).…”
Section: Intersecting Cultural Identities In Health Psychologymentioning
confidence: 99%
“…According to Redmond et al ( 2017 , p. 312), both African-American and African-Caribbean groups report avoiding treatment for substance abuse due to wanting to solve their own problems, and not identifying a need for outside help. However, African-Americans were more likely to seek help from professionals than African-Caribbean women (Redmond et al, 2017 , p. 312). The reluctance of help-seeking behaviors for African-Caribbean women in the U.S. align with the experiences of other women of African-Caribbean descent in the U.K. and Canada (Nestel, 2012 ; Office for National Statistics, 2018 ).…”
Section: Intersecting Cultural Identities In Health Psychologymentioning
confidence: 99%
“…Siqueland et al () found non‐Hispanic Whites were 62% more likely to complete substance use treatment intake compared to 44% of African Americans. Based on a national sample of Black Americans, female participants often reported they did not seek help because they felt their problems were not serious enough, while males did not seek help because they thought things would get better (Redmond, Watkins, Broman, Abelson, & Neighbors, ). The issue for African Americans whether male or female is once in treatment, they do not complete the entire treatment process and have shorter treatment durations compared to White Americans (Breslau et al, ; Ojeda & McGuire, ; Schmidt, Greenfield, & Mulia, ).…”
Section: Introductionmentioning
confidence: 99%
“…Despite increased stressors, BIPOC continued to experience structural barriers that precluded their mental health help-seeking efforts. Notably, there is a dearth of access to culturally salient interventions, a paucity of quality of mental healthcare, increases costs for service, and challenges related to health insurance (Burkett, 2017 ; Hankerson et al, 2015 ; Hudson et al, 2018 ; Nicolaidis et al, 2010 ; Redmond et al, 2017 ; Waller et al, 2022a ; Woodward et al, 2008 ).…”
Section: Introductionmentioning
confidence: 99%